2010
DOI: 10.1001/archoto.2009.187
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Complications in Pediatric Cochlear Implantation

Abstract: Complications of CI in children are common, with trauma as a major factor. Inner ear malformations should prompt specific preventive management. Cochlear implantation in young children did not appear to be a risk factor in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 36 publications
0
55
1
6
Order By: Relevance
“…However, CI complications may require specific attention to treat. In a recent retrospective study from France, the overall rate of complications was 9.9% in 434 patients underwent CI, with major complications accounting for 5.5% (24/ 434) [1]. Another study showed that the overall rate of complications was 16.0% (79/500), with minor complications accounting for 5.6%; major complications, 3.2%; and reimplantations, 7.2% [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, CI complications may require specific attention to treat. In a recent retrospective study from France, the overall rate of complications was 9.9% in 434 patients underwent CI, with major complications accounting for 5.5% (24/ 434) [1]. Another study showed that the overall rate of complications was 16.0% (79/500), with minor complications accounting for 5.6%; major complications, 3.2%; and reimplantations, 7.2% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Только 15 пациентам потребова-лась ревизионная хирургия, тогда как 3 пациента полу-чили местное консервативное лечение. осложнений в виде серомы или гематомы у взрослого населения очень низкая [9,10]. В нашем исследовании малые осложнения в виде гематомы выявлены у 0,5% оперированных пациентов.…”
Section: Discussionunclassified
“…Loundon et al выявили 4 случая среднего отита среди 434 имплантиро-ванных пациентов. Из них двое лечились только антибио-тиками, а двум пациентам потребовалось шунтирование среднего уха [9,10]. В нашем исследовании частота воз-никновения среднего отита после КИ составила 0,2%.…”
Section: Discussionunclassified
“…For children with anatomical deformities of the cochlea (such as Mondini deformity, in which there are less than the normal two and a half turns in the cochlea), the risk of facial nerve damage is greater. However, reported major complication rates are very low, ranging from 2 -5% (Bhatia et al, 2004;Cohen et al, 1989;Loundon et al, 2010).…”
Section: Risksmentioning
confidence: 99%
“…The incidence of minor complications is higher and more subject to variation between cochlear implant centers; studies of large numbers of patients ranging from 4% -20% (Bhatia et al, 2004;Dutt et al, 2005;Loundon et al, 2010). Other risks include those of any surgical procedure, including the risks associated with an anaesthetic and blood loss.…”
Section: Risksmentioning
confidence: 99%